Evaluating Advancements in Forensic Medicine and Toxicology Through a Scientometric Mapping (Sciences of Pharmacy, 2023)
The study focused on using scientometric methods to analyze forensic medicine and toxicology literature. The selected period for the study was from 2013 to 2022, allowing for a recent and comprehensive field analysis. The study used bibliographic data from a PubMed database, a widely used biomedical literature database. The study aimed to provide a comprehensive picture of the production and dissemination of the literature in the field. To achieve this, the study analyzed various bibliometric indicators, including theme analysis, keyword evolvement, and collaboration map. The analysis of trending topics and future thematic directions in the field was also conducted to provide insight that could inform and stimulate the research interests of young researchers. This scholarly article explains the construction of author networks, the assessment of author productivity yearly, and the analysis of affiliation networks and organizations. The number of articles published by an institution is an essential indicator of research productivity and expertise in the particular field. The study's findings provided valuable insights into the trends and patterns in forensic medicine and toxicology.